(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article will focus on the formation of Uzbek terms in the information and communication sphere. Today in our life there are a lot of different mobile devices, different gadgets, and their names are mostly borrowed words and terms. The problem is how to translate them into Uzbek, if the gadget itself entered our lives from outside with its own name. There are two-word, three-word, even four-word terms. In such cases, the keyword can be left, and the rest can be translated, or the foreign name of the device can be combined with an Uzbek derivational affix. The article discusses different options for the formation of Uzbek terms